Les journaux anglophones sous la Révolution française - Simon Macdonald (Etudes Epistémè)
This article examines a series of English-language newspaper ventures produced in revolutionary France and largely aimed at export to Britain. These enterprises, chief among which was the Paris Mercury (1792), sought to profit from heightened British interest in French events by dispatching ready-printed newspapers directly from Paris, thus achieving news priority over the domestic British press. New French press freedoms also enabled claims to be made about the superior editorial qualities of such extraterritorial newspapers. This article reconstructs these newspapers’ publication history, reviews their contents, discusses their commercial and political rationale and their precursors, and offers explanations for their failure.